Pendidikan Digital: Meningkatkan Keterampilan TIK Siswa SMK Pariwisata Aik Bual Untuk Menghadapi Dunia Kerja - Ardhana, Valian Yoga Pudya; Mulyodiputro, M. Dermawan (P3M Politeknik Negeri Jember, 2025)
Aik Bual Tourism Vocational School in Central Lombok Regency is an educational institution managed by a foundation which has the responsibility to equip its graduates with skills that suit the needs of the tourism industry. In this context, digitalization has an important role in improving the quality of education and preparing students to face challenges in the world of work. However, the challenges faced by Aik Bual Tourism Vocational School students are not small. There are still many students who do not understand how to use technology optimally, both in academic and practical contexts. Therefore, appropriate and targeted digital education needs to be implemented to equip students with the necessary ICT skills. Through training programs and optimal use of digital resources, it is hoped that students can improve their capabilities and be ready to compete in an increasingly dynamic job market. This community service activity aims to improve the ICT skills of Aik Bual Tourism Vocational School students. with a systematic and technology-based approach. The results obtained in this community service activity were an increase in students' ICT skills, where before the training, only 35% of students had basic knowledge about ICT. After training, this figure increased to 85%, indicating progress. Then the training material which includes the use of social media and digital marketing is very suited to the needs of the tourism industry, which requires a workforce skilled in using digital platforms for promotion and communication. And most importantly students demonstrated a significant increase in confidence in their ability to manage digital projects, which was reflected in successful and engaging group-based project outcomes.